Decoding Spinoza: Navigating Essence and Existence through Gnoseological Lens - García Ruzo, Antonieta (Conatus - Journal of Philosophy, 2024)
This work aims to depart from conventional interpretations of Spinoza’s notions of essence and existence by offering an alternative perspective called the onto-gnoseological reading. Typically, these concepts of essence and existence are approached from an ontological standpoint or are simply disregarded. The objective of this paper is to demonstrate that Spinoza, within his corpus associates these notions with the activity of the genres of knowledge rather than with the ontological realm. This reinterpretation of the concepts from a gnoseological standpoint allows for a deeper comprehension of Spinoza’s philosophical undertaking. It becomes evident that this project involves the coexistence of gnoseological duality in perfect harmony with the univocity of reality, serving as a crucial instrument for recognizing the boundaries and possibilities of human knowledge and, subsequently, the potential for achieving human virtue.